EMPLOYEE INFORMATION SYSTEM USING AHP (ANALYTICAL HIERARCHY PROCESS) METHOD IN DINAS OF INVESTMENT AND INTEGRATED SERVICES ONE DOOR OF KEBUMEN DISTRICT - Waluyo, Ari; Irfandi, Nur Fais (Jurnal E-Komtek (Elektro-Komputer-Teknik), 2017)
The technology is growing at the moment strongly supporting the needs of an agency. It’s for realizing the effectiveness and efficiency as well as in improving services to the public. Especially systems that can assist in providing information and decisions in selecting of the best employee / role model to spur the employee performance. Department of Investment and Integrated Services One Stop Kebumen is one in which government agencies in determining the best employee / exemplary still running manual. There are several obstacles that occur in the process of employee assessment and the possibility of inaccurate assessment performed by employees. Of the reasons the author tries to provide alternatives troubleshooting’s is to build the human resources system using AHP (Analytical Hierarchy Process) with the aim of selecting the best employee / department exemplary in investment and one door integrated services Kebumen district. With the Human Resources Information System Using Method of AHP (Analytical Hierarchy Process) can help decisions in selecting the best employee / exemplary at the Department of Investment and Integrated Services One Stop Kebumen.